The Role of p53 Gene In Molecular Pathogenesis of Oral Squamous Cell Carcinoma - Nabilla, Firyal; Hadikrishna, Indra; Yusuf, Harmas Yazid (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Oral squamous cell carcinoma is the most common malignant tumor in oral and originates from the epithelial tissue. Carcinoma formation is a genetic process that triggers changes in cell morphology and behavior. Abnormalities in cell cycle control, regulated by p53 among these factors. This study was conducted to examine the role of p53 and p53-related proteins in the formation of oral squamous cell carcinoma. Review: p53 is a component of the genome associated with the development of cancer in humans. Several studies have suggested that p53 is an important antitumor weapon. In the cell cycle, p53 is recognized if there is a cell mutation or the presence of an oncogene, and delays the cell cycle to prevent cells from becoming cancerous. The level of p53 will increase and react by arresting the cell cycle, directing cells to repair or undergo apoptosis. If p53 does not function, the cell cycle carrying damaged genetic material continues and is unable to undergo apoptosis. As a result, cells continue to proliferate with genetic abnormalities that can lead to malignancy. Conclusion: Loss of p53 function can cause random mutations, chromosomal changes, and aneuploidy, which drive the growth of cancer cells to a malignant state. Analysis of changes at the molecular level can be a major diagnostic tool to guide treatment and identify changes associated with oral squamous cell carcinoma.